Willingness to pay for conservation fee at Penang National Park - Samdin, Zaiton; Mohammad Afandi, Syamsul Herman; Radam, Alias; Yacob, Mohd Rusli (Forestry Department Peninsular Malaysia, 2012)
Contingent Valuation Method (CVM) is one of the approaches that have helped to assign dollar values to non-use values for non-market goods. Most of ecotourism areas such as national parks exist as public facilities. Some national parks have implemented charges such as entrance permit to visitors but it still creates problems especially for the pricing system thus related to efficient pricing policy and the sustainability of ecotourism resources. The introduction of efficient pricing policy for the utilization of parks should be given special attention, especially in developing countries. This study used the CVM, with Willingness to Pay (WTP) as the elicitation method to measure non-use value for environmental resources in Penang National Park. A total of 509 respondents completed the survey. The finding of this study discovers that visitors are willing to pay for the conservation fee. Recently, there is no charge for conservation fee. Although using WTP for economic valuation cannot provide the exact answers on the valuation of these natural resources, it can still provide a guideline on pricing strategy and postulate extra information for park management decisions, especially on park pricing.